Be compassionate with your socially anxious mind: shame, self-criticism and self-compassion in the relationship between self-focused attention and social anxiety in adolescents - Cabete, Natacha Sousa (2016)
Dissertação de mestrado em Psicologia (Intervenções Cognitivo-Comportamentais nas Perturbações Psicológicas e Saúde) apresentada à Faculdade de Psicologia e de Ciências da Educação da Universidade de Coimbra